Intervensi Edukasi tentang Asma dengan Media Leaflet terhadap Pengetahuan Ibu - Afifah Nur Fitri Widyasari; Irdawati Irdawati (Jurnal Keperawatan Silampari, 2023)
This study aims to determine the effect of health education using leaflet media on the level of knowledge of mothers under five in Dusun Bratan. The method used in this research is pre-experimental with the type of pre-post test research in one group (one-group pre-post test design). The study's results using the Wilcoxon Rank Test showed a difference between the pre-test knowledge score before health education was carried out and the post-test knowledge score after being given health education. In conclusion, there is an effect of health education using leaflet media on the level of knowledge of mothers under five in Bratan Hamlet, Pajang District, Surakarta City, Central Java Province. Keywords: Asthma, Leaflet, Knowledge